Rancang Bangun Sistem Informasi Pemetaan Kamar Pondok Pesantren Amanatul Ummah - Anam, Khoirul; Wibowo, Achmad Teguh; Milad, Mohammad Khusnu (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
In this research discusses the implementation of GIS to solve the problems that often occur in Islamic Boarding Schools, especially Islamic Boarding Schools of Amanatul Ummah Surabaya. The problem faces at Amanatul Ummah is still using the manual system in determining rooms for new students, so many rooms in this Islamic boarding school an overcapacity. The alternative solution to this problem is to develop a system that could be mapping and know the capacity of each room along with the number of room occupants so that to reduce excess capacity. This application can help determine and show the capacity of each room because the safety and comfort of student in Islamic Boarding School could be influenced by health and social factor. Other than that a vision of the Amanatul Ummah especially superior, whole, and glorious of a human being can be achieved